Environmental Vulnerability in Food Estate Policy in Central Kalimantan: Political Ecology Review - Churrin In; Shan Evanthe; Nafisa D; Farhan Idris; Iradhad Sihidi (Indonesian Journal of Public Administration Review, 2026)
This study aims to analyze the implementation of Indonesia’s food estate policy in Central Kalimantan and assess its ecological and social implications from a political ecology perspective. Using a qualitative case study design, data were collected through documentary analysis of policy documents, official government reports, scientific publications, and media coverage. The study examines power relations among the state, corporations, and local communities to understand how governance arrangements shape policy outcomes. The findings reveal that the food estate program operates within an unequal power structure that prioritizes state and corporate interests over local livelihoods. Policy implementation has generated significant ecological vulnerabilities, including deforestation, peatland degradation, disruption of hydrological systems, and increased risks of long-term environmental crises. Social impacts are also evident in the marginalization of indigenous peoples and smallholder farmers due to limited participation, reduced land access, and inequitable benefit distribution. These results indicate that the food estate policy functions not merely as a technocratic strategy for food security but as a political arena that redistributes environmental risks and socio-economic burdens toward local communities. The study highlights the need for governance reforms that integrate ecological sustainability, social justice, participatory decision-making, and recognition of local knowledge to ensure more equitable and sustainable agricultural development.